2016
DOI: 10.1155/2016/8483537
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability as Early Biomarker for the Evaluation of Diabetes Mellitus Progress

Abstract: According to the American Diabetes Association (ADA), the side effects of diabetes mellitus have recently increased the global health expenditure each year. Of these, the early diagnostic can contribute to the decrease on renal, cardiovascular, and nervous systems complications. However, the diagnostic criteria, which are commonly used, do not suggest the diabetes progress in the patient. In this study, the streptozotocin model in mice (cDM) was used as early diagnostic criterion to reduce the side effects rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Heart rate variability (HRV) is a commonly noninvasive autonomic biomarker used in clinical protocols (Beauchaine & Thayer, ; Task Force, ; Thayer & Lane, ; Thayer, Åhs, Fredrikson, Sollers, & Wager, ). The quantitative values obtained by R–R intervals analysis has reliability to distinguish patients with obesity (Iliescu, Tudorancea, Irwin, & Lohmeier, ; Yadavet al, ), diabetes (Arroyo‐Carmonaet al, ; Dimitropoulos, ), psychiatric disorders (Chalmers, Quintana, Abbott, & Kemp, ), and others specific situations (for a review see Thayer & Lane, ; Thayeret al, ;), when the impairment of vagal tone regulation is reported as a common biomarker for these clinical conditions (Laborde, Mosley, & Thayer, ; Thayer & Lane, ,). In order to obtain reliable data for the HRV quantitative analysis, it is recommended to carry out recordings with 5 min or longer, according to the research design (Labordeet al, ; Task Force, ).…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) is a commonly noninvasive autonomic biomarker used in clinical protocols (Beauchaine & Thayer, ; Task Force, ; Thayer & Lane, ; Thayer, Åhs, Fredrikson, Sollers, & Wager, ). The quantitative values obtained by R–R intervals analysis has reliability to distinguish patients with obesity (Iliescu, Tudorancea, Irwin, & Lohmeier, ; Yadavet al, ), diabetes (Arroyo‐Carmonaet al, ; Dimitropoulos, ), psychiatric disorders (Chalmers, Quintana, Abbott, & Kemp, ), and others specific situations (for a review see Thayer & Lane, ; Thayeret al, ;), when the impairment of vagal tone regulation is reported as a common biomarker for these clinical conditions (Laborde, Mosley, & Thayer, ; Thayer & Lane, ,). In order to obtain reliable data for the HRV quantitative analysis, it is recommended to carry out recordings with 5 min or longer, according to the research design (Labordeet al, ; Task Force, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while HRV analysis is mainly associated with the prediction of sudden cardiac death [21,22] and with assessing cardiovascular [23] and metabolic illness [24] progression, recent observations have suggested it is also applicable to exercise and training [25]. During physical exercise, interactions occur between the cardiovascular system, the respiratory system, and the muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of biological variability has been used to study several physiological phenomena, among them, fluctuations on the heart rate using the RR interval period of the electrocardiogram (ECG). The heart rate variability (HRV) is a useful health indicator [3], and in this chapter we detail how this tool is used for the prognosis and diagnosis of metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%